TURNAROUND TIME OF DIAGNOSTIC LABORATORY RESULTS AS A QUALITY IMPROVEMENT TO PATIENT SATISFACTION: A SYSTEMATIC LITERATURE REVIEW - Purbosari Purbosari; Ede Surya Darmawan (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Laboratory information is increasingly recognized as a crucial factor to reduce diagnostic uncertainty and enhance quality care. Medical diagnoses and effective treatments depend on the accurate and timely reporting of laboratory test results, and the trend toward disease prevention and personalized care calls for more complex and effective tests and biomarkers. Today's clinical laboratory provides essential information for the diagnosis, monitoring, screening, prevention, early diagnosis, tailored treatment and more effective monitoring of human diseases. Response Time is an action that is carried out quickly and precisely to handle patients. While an ability for fast (responsive) service is the response time taken to the patient when the patient arrives to get a response. Response time is one indicator of service quality that affects patient satisfaction. The laboratory turnaround time is the starting point for the time of for receiving the sample, the time for registration, or the analytical sampling time and end point for analytical completion, the time for verification of results, the transfer of results to the time for medical record, and the time for report printing. Methods: In this systematic review, we searched Pubmed, Science Direct, and Scopus database published from January 2010 to March 2019. The included studies were broadly classified as reporting from healthcare/hospital and international survey. There were 21 studies that met keywords searching criteria. Then we analysed based on the content of studies, matching to our objectives Results: Out of 21 identified studies, we recognized 6 scholarly journals of turnaround time diagnostic laboratory results as quality improvement of medical care and medical diagnoses and that affects patient satisfaction. These studies concluded that turnaround time becomes a key element to patient safety that contributes to patient satisfaction. Conclusion: Turnaround time as one of quality indicator in a laboratory setting. Improvement in this parameter could give benefit to the patient and deliver service excellence. Standardized reporting method is mandatory as it will not only allow the accreditation of clinical laboratories according to the International Standard but also to assure guidance for promoting improvement processes and guaranteeing quality care to patients and patient satisfaction.